THE INFLUENCE OF MOTHER TODDLER CLASS ON MOTHER'S KNOWLEDGE AND SKILLS REGARDING THE STIMULATION OF THE GROWTH AND DEVELOPMENT OF TODDLER CHILDREN IN THE WORKING AREA OF THE KUTA MAKMUR HEALTH CENTER - Rahmisyah; Zurriyati Armawi (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Late detection of growth and development deviations will be more difficult to intervene and will affect children's growth and development. Mothers must be equipped with sufficient knowledge and skills to stimulate child growth and development. To determine to improve mothers' knowledge and skills about stimulating toddler growth and development, namely by conducting the Toddler Mother Class (KIB). Research design using quasy experiment design (one group pretest–postest). The population was 129 people with a sample of 56 respondents. The sampling method is accidental sampling using the wilcoxon test. There is an influence of the mother toddler class on mothers' knowledge and skills about stimulating the growth and development of children under five in the work area of the Kuta Makmur Health Center. It is hoped that this research is useful and used as information material to add insight, comparison and reference to conduct further research, especially for midwifery researchers who will research and become a reference for further research by adding research variables and broader research objects.